Komunikasi dan Pola Asuh Anak Balita - Remaja dalam Keluarga Betawi Jakarta dan Bekasi - Afrina Sari (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2014)
This research aims to test the significant differences the use of family communication and the pattern of childcare toddlers and teenagers in families living in the Kampung Tugu in north Jakarta, Kampung Condet in East Jakarta and Ujung Harapan in bekasi. This study using quantitative methods of correlational. The results of research shows that the communication in childcare on the community in Kampung Tugu of north Jakarta, more affected from ways obtained from earlier the generations. The average betawi people in their religious pillar of the nazarenes, some are muslim. For people who follow the Islamic religion, they to develop a pattern of parenting in the family in Islamic way. The Betawi Community of Kampung Condet in East Jakarta, further develop ways a family tradition which are influenced by arab cultures ways. So they develop more into islamic ways. Also betawi people on Kampung Ujung Harapan in Bekasi, almost the entire community on Kampung Ujung Harapan Bekasi are moeslim. So that childcare more patterns dominated by islamic ways which were inherited from earlier generations. A pattern to the consistence of parenting in educating if compared between toddlers and teenagers, the community in Kampung Tugu more dominant educate young teen, while the Kampung Condet and Kampung Ujung Harapan directing consistency educate in toddlers and teenagers.